Impacts of Forest Bathing (Shinrin-Yoku) in Female Participants with Depression/Depressive Tendencies - Qing Li; Norimasa Takayama; Masao Katsumata; Hiroshi Takayama; Yukako Kimura; Shigeyoshi Kumeda; Takashi Miura; Tetsuya Ichimiya; Ruei Tan; Haruka Shimomura; Amane Tateno; Tsunemi Kitagawa; et al. (Diseases)
Background: It has been reported that forest bathing significantly reduced negative emotions and increased the positive feelings in both healthy males and females, as well as increasing blood serotonin in healthy males, indicating the potential for a beneficial effect on depressive status. However, an improvement effect of forest bathing on participants with depression has not been reported so far. Therefore, in order to fill this gap, this study examined the effect of forest bathing on depression in female participants with depression/depressive tendencies. Methods: Thirty-one females aged 40.1 ± 2.4 years with depression/depressive tendencies were recruited after obtaining informed consent. The study employed a randomized crossover design to compare forest bathing with city walking. They participated in day trips to a Japanese cypress forest park and to a city area of Nagano Prefecture as a control in June 2023. On both trips, they walked 2.5 km (for 90 min) in the morning and afternoon, respectively, for a total of 5.0 km per day. Blood samples were taken at 4 pm for the measurements before forest bathing on the first day and after the walking in forest and unban sites on the second and third days, at the same hospital. Concentrations of oxytocin, IGF-1, serotonin and lactic acid in blood were measured. SDS scores were calculated and the POMS test and questionnaires for subjective fatigue symptoms and sleep quality were administered before and after each trip. Temperature, humidity and illuminance were also measured in the forest and urban environments. The Nippon Medical School Central Ethics Committee approved this study. Results: Forest bathing significantly decreased SDS scores compared to city walk and the baseline, and the effect lasted for one week after forest bathing. Forest bathing also significantly increased the concentrations of blood serotonin in participants who were not taking antidepressants, significantly increased the levels of oxytocin and IGF-1 in blood, significantly increased the scores for positive feelings, and reduced the scores for negative emotions compared with city walking in the POMS test. In addition, forest bathing reduced subjective fatigue symptoms and improved sleep quality. Conclusions: These findings provided scientific evidence to contribute to understanding forest bathing as a potential intervention for preventing depression, and future research on males should further explore these effects.